Association between dietary carbohydrate intake quality and micronutrient intake adequacy in a Mediterranean cohort: the SUN (Seguimiento Universidad de Navarra) Project. Issue 11 (14th June 2014) - Zazpe, Itziar; Sánchez-Taínta, Ana; Santiago, Susana; de la Fuente-Arrillaga, Carmen; Bes-Rastrollo, Maira; Martínez, J. Alfredo; Martínez-González, Miguel Ángel
<x content-type="archive" xml:space="preserve">Abstract</x> Epidemiological research confirms that the prevalence of suboptimal micronutrient intakes across Europe is an emerging concern in terms of public health. The aim of the present study was to investigate the association between a new index of carbohydrate (CHO) quality and micronutrient intake adequacy in the 'Seguimiento Universidad de Navarra (SUN)' cohort. The baseline assessment extended from 1999 to March 2012. We assessed 16 841 participants who completed a validated 136-item semi-quantitative FFQ at baseline. We created a new index to evaluate CHO quality for the following four criteria: dietary fibre intake; glycaemic index; whole grains:total grains ratio; solid CHO:total CHO ratio. The subjects were classified into quintiles according to this index. We evaluated the intakes of Zn, I, Se, Fe, Ca, K, P, Mg, Cr and vitamins B1, B2, B3, B6, B12, C, A, D, E and folic acid. The probability of intake adequacy was evaluated using the estimated average requirement cut-point approach and the probabilistic approach. Logistic regression analysis was used to assess the nutritional adequacy according to the CHO quality index (CQI). Participants in the highest quintile of CQI were found to have the lowest prevalence of inadequacy. A higher quality of CHO intake was found to be associated with a lower risk of nutritional inadequacy in comparison with the lowest quintile of CQI (adjusted OR 0·06, 95 % CI 0·02, 0·16; P for trend < 0·001). A higher CQI was found to be strongly associated with better micronutrient intake adequacy in the young Mediterranean cohort, stressing the importance of focusing nutritional education not only on CHO quantity, but also on quality.